Assessment of Environmental Quality of an Area Adjacent To the Relocated Tannery Inustries at Hemayetpur, Bangladesh (Dhaka University Journal of Biological Sciences, 2022)
The deterioration of environmental quality due to wastes generated from tannery industries is an alarming global issue in Bangladesh. To assess this problem in an area adjacent to the recently shifted tannery industries at Hemayetpur, soil, water and plant samples are collected from upstream as control, secondary treatment ponds, main discharge station and downstream at 500, 1000, 2000 and 3000 m across the areas and are analyzed for environmental quality. The water samples of Dhaleswari river are slightly acidic to moderately alkaline pH from 6.55 to 10.60, high TDS from 176 to 10,433 mg/l, EC from 305 to 18,206 μS/cm, nitrate from 0.14 to 194 mg/l, sulfate from 10.72 to 8922 mg/l, moderate phosphate from 0.58 to 7.2 mg/l and low DO from 1.61 to 5.50 mg/l. It is clearly noticed that most of the water parameters exceeded WHO guideline values except pH and phosphate that indicates Dhaleswari river water quality is declining slowly. The available concentrations of nitrogen, phosphorus, potassium and sulfur in soil varies from 12 to 263, 1.19 to 38, 17 to 170, 251 to 680 mg/kg, respectively, whereas, the total concentration ranges from 0.03 to 0.14%, 0.090 to 0.14%, 0.12 to 0.48%, and 0.11 to 0.42%, respectively. In soil samples, total phosphorus and potassium concentrations are increased but sulfur decreased. The soils are found acidic in nature that have high EC 8.17 dS/m. A significant positive correlation is found with each other of nitrogen, phosphorus, potassium and sulfur concentrations in soil samples. The nutrients in plant samples have no deficiency those are within the optimum range.Dhaka Univ. J. Biol. Sci. 31(1): 29-43, 2022 (January)